Analysis of Fatwa Regarding Sharia Credit Cards and Their Relevance to the Development of Islamic Banking in Indonesia and Bahrain - Suci Ramadhan; Toguan Rambe; Badai Husain Hasibuan; Abdul Aziz Harahap (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2023)
This research aims to analyze fatwas on Sharia credit cards and their relevance to the development of Islamic banking in Indonesia and Bahrain. This qualitative study uses a text and context approach. The main data used are fatwas from DSN-MUI and the Sharia Supervisory Board of Bank Islam Bahrain regarding Sharia credit cards, supported by books, scientific articles, and reports on the development of Islamic banking. Data were collected through documentation techniques and analyzed using descriptive analysis. This study concludes that Sharia credit cards, as outlined in the fatwas of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) and the Sharia Supervisory Board of Bank Islam Bahrain (SSB-BIsB), are permissible as transaction tools based on legal principles, contract provisions, wage and service provisions, penalties, and limits in accordance with Sharia principles. Specifically, in Bahrain, fatwas must refer to the standards of the Accounting and Auditing Organization for Islamic Finance Institutions (AAOIFI). Currently, the use of Sharia credit cards in Bahrain is experiencing significant growth, while in Indonesia, public interest in using Sharia credit cards remains relatively low. The findings of this research can serve as policy studies for fatwa institutions and Islamic banking to enhance the growth of Sharia credit cards as a Sharia financing instrument for the public, particularly in Indonesia.